PERITONEAL DIALYSIS TO TREAT PATIENTS WITH ACUTE KIDNEY INJURY—THE SAVING YOUNG LIVES EXPERIENCE IN WEST AFRICA: PROCEEDINGS OF THE SAVING YOUNG LIVES SESSION AT THE FIRST INTERNATIONAL CONFERENCE OF DIALYSIS IN WEST AFRICA, DAKAR, SENEGAL, DECEMBER 2015 - Niang, Abdou; Antwi, Sampson; Adonis Koffi, Laurence; LALYA, HONORAT FRANCIS; May Adabayeri, Victoria; NYAH, Norah; Palmer, Dennis; Brusselmans, Ariane; Cullis, Brett; Feehally, John; McCulloch, Mignon; Finkelstein, Fredric (My University, 2017)
In December 2015, as part of the First African Dialysis Conference organized in Dakar, Senegal, 5 physicians from West African countries who have participated in the Saving Young Lives Program reviewed their experiences establishing peritoneal dialysis (PD) programs to treat patients with acute kidney injury (AKI). Thus far, nearly 200 patients have received PD treatment in these countries. The interaction and discussion amongst the participants at the meeting was meaningful and informative. The presentations highlighted the creativity, conviction, and determination of the physicians in overcoming the various barriers and challenges they encountered to establish PD/AKI programs. Hopefully, these successes and the increased awareness of the importance of early diagnosis and treatment of AKI will inspire much needed support from government, hospital, and international organizations.
Keywords: Peritoneal dialysis; acute kidney injury; africa; saving young lives